PENGARUH HARGA TERHADAP JUMLAH PERMINTAAN PADA PT. TOYOTA HADJI KALLA CABANG PAREPARE - Sakri, Sardi (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of price on the amount of demand at PT. Toyota Hadji Kalla Cabang Parepare 2017-2018. The data collection techniques used in this study were interviews and documentation. The sample in this study amounted to 26 respondents who were involved in sales reports. The data analysis technique in this study is to use simple linear analysis. The result of this research shows that price affects the amount of demand at PT. Toyota Hadji Kalla Cabang Parepare